دراسة قوة الهجين والمقدرة العامة والخاصة على الائتلاف للغلة وعناصرها لدى أصناف متعددة من القمح الطري Triticum aestivum - معلا, محمد; حربا, نزار (Latakia University Journal -Biological Sciences Series, 2019)
نفذت هذه الدراسة لموسمين متتاليين 2007/2008 و2008/2009 بهدف دراسة قوة الهجين والقدرة على الائتلاف لأربعة أصناف سورية (شام 4، بحوث 6، شام 6، السلالة الطافرة L92) وصنفين مصريين من الأقماح الطرية (جيزة 157/ جيزة 162)، وأجري التهجين التبادلي بينهما، وإمكانية اختيار أفضل الأصناف والهجن الناتجة منها ذات القيمة الموجبة للمقدرة الخاصة على الائتلاف والحاصلة من الفعل (التراكمي التراكمي). زرعت الهجن مع آبائها وفق تصميم القطاعات العشوائية الكاملة بثلاثة مكررات لتقدير القدرة العامة على التوافق GCA، والقدرة الخاصة على التوافق SCA، وقوة الهجين بالنسبة لكل من متوسط الأبوين والأب الأعلى للصفات: عدد الإشطاءات المثمرة، طول الساق الرئيسة، طول السنبلة، عدد السنيبلات/بالسنبلة، عدد الحبوب/السنبلة، وزن الحبوب/السنبلة، وزن الألف حبة، الغلة الحبية/النبات. أظهر الهجين N10 (L92 × جيزة 162) قوة هجين موجبة وعالية ومقدرة خاصة مرتفعة على الائتلاف ناتج من ائتلاف أبوين: سلالة طافرة سورية L92 موجبة في قدرتها العامة وصنف مصري ج 162 موجب في قدرته العامة على الائتلاف في صفة الغلة الحبية/النبات. This study was carried out during the two growing seasons (2007 – 2008 ; 2008 – 2009). The main objective was to study heterosis and combining ability in four Syrian varieties (Sham4 – Bohouth6 – Sham6 – mutant line L92) and two Egyptian bread wheat (Geza 157 and Geza 162) used in diallel cross. The possibility of choosing the best varieties and derived hybrids positive for SCA of the type additive x additive gene action were also examined. The crosses were grown along with their parents in a randomized complete block design (RCBD) with three replications to estimate general combining ability (GCA), specific combining ability (SCA) and both med - and high - parent heterosis for number of fertile tillers. main stem height, spike length, no. of spikletsl/ spike, no. of grain/ spike, grain wt./ spike, 1000 grain wt. ; and grain yield / plant. The hybrid (N10) derived from the cross (L92 X Giza 162) showed high positive heterosis potential and SCA for grain yield plant of both parents exhibited positive GCA for this trait.